2000
DOI: 10.4133/jeeg5.2.21
|View full text |Cite
|
Sign up to set email alerts
|

Fast Estimation of Parameters of a Layered-dipping Earth Model by Inverting Reflected Waves

Abstract: Shallow high-resolution reflection data provide information about near-surface geology from 20 m to 300 m depth. Within a receiver-spread range of 10 m to 150 m, a layered-dipping earth model is a simple and valid model in most cases of shallow reflection surveying. We formulated an approach to quickly estimate parameters such as interval velocity, reflector depth, and dip by inverting reflected traveltime of a layered-dipping earth model. To reduce the ambiguity of inverted solutions, we apply constraints on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…2). This model is common in mapping bedrock and any significant alluvial/colluvial acoustic contrasts between the bedrock and the ground surface in shallow reflection survey (e.g., Miller et al 1995;Xia & Miller 2000). An inverted velocity model by travel time inversion of real data acquired in Lake Tahoe, California, showed that velocities change from 1000 m/s to 1800 m/s in the top 200 m of the Earth (Xia & Miller 2000).…”
Section: Velocity Analysis Of a Synthetic Multi-flat-subsurface Modelmentioning
confidence: 99%
“…2). This model is common in mapping bedrock and any significant alluvial/colluvial acoustic contrasts between the bedrock and the ground surface in shallow reflection survey (e.g., Miller et al 1995;Xia & Miller 2000). An inverted velocity model by travel time inversion of real data acquired in Lake Tahoe, California, showed that velocities change from 1000 m/s to 1800 m/s in the top 200 m of the Earth (Xia & Miller 2000).…”
Section: Velocity Analysis Of a Synthetic Multi-flat-subsurface Modelmentioning
confidence: 99%
“…After each iteration the model is appropriately modified and the process continues until convergence, that is when further model updates do not affect the mismatch error E(x) (difference between the observed and calculated data). Deterministic methods were employed to provide stable solutions to inverse problems such as surface wave dispersion-curves inversion to find S-wave velocities (XIA et al, 1999(XIA et al, , 2003 and surface wave attenuation-curve inversion to find quality factors of near-surface materials (XIA et al, 2002) and to improve stability of inverse processing to an inverse problem of reflection travel time (XIA and MILLER, 2000). Convergence occurs when the inversion iterative process reaches a mismatcherror minimum.…”
Section: Introductionmentioning
confidence: 99%